Modification of Metal Microelectrodes with Vertical Graphene Structure for Enhanced Electrochemical Detection of Dopamine - Lukang Gao; Shuang Huang; Xiaotong Li; Zhengjie Liu; Xinshuo Huang; Yan Li; Hui‐jiuan Chen; Xudong Lin; Jing Liu; Xi Xie (Advanced Materials Interfaces)
Abstract Detection of dopamine (DA) concentration can reflect important aspects of human brain health, including the nervous system and endocrine. Among various methods for detecting DA concentration, electrochemical detection is a promising method to allow in situ and real‐time sensing. Besides, nanomaterials modification on microelectrodes is beneficial to enhance the electrochemical detection performance. In this study, microwire electrodes are modified with vertical graphene (VG) through plasma‐enhanced chemical vapor deposition, which is based on 4 types of electrode substrates (Au, Ti, Ag, and W). The sensing performance of DA concentrations is explored with different electrochemical methods, including EIS, CV, DPV, SWV, LSV, and NPV. The modification of VG improved the sensitivity of both Au and Ti microelectrodes and decreased the oxidation peak potentials. VG‐modified Au microelectrode exhibited the most pronounced reduction (by 50.8%) in the peak potential of the DPV curve, while VG‐modified Ti microelectrode showed the most improvement of the sensitivity (by 9140%) in SWV detection. In summary, the results demonstrated that functionalization with VG is an effective way to improve the electrochemical sensing capability among different types of electrode substrates. This is beneficial for developing high‐performance microelectrodes for in vivo detection of DA concentrations.